Analisis Faktor-Faktor Terjadinya Pernikahan di Bawah Umur - Lina Ustikorini; blognulis (HOKI : Journal of Islamic Family Law, 2025)
Underage marriage is still a social problem in many parts of Indonesia. This research uses a qualitative approach to reveal the factors that cause early marriage in Ujungpangkah. The research method uses a qualitative approach. The findings show that poverty, promiscuity, weak parental supervision, and misuse of technology are the dominant factors. In addition, marriage dispensation through religious courts also reinforces this practice even though the minimum age limit for marriage has been regulated in Law No. 16/2019. Interestingly, in some cases early marriage does not always result in divorce, although long-term risks related to education, mental and health remain a concern.